The two-dimensional effects of Salvadora persica mechanical brushing on the surface of polymethyl methacrylate denture base material - Wan Nor Syariza Wan Ali; Sapon M.S; Rosdi N.M; Halib N.; Mohamed N. (University of Dicle, 2024)
Indexed by Scopus